An Analysis Of Biomass Power Generation From Waste With Briquette - Maneger Lubis; Solly Aryza; Siti Anisah (Sean Institute, 2024)
The increasing demand for electricity and the efforts to reduce the environmental impact of waste drive the development of biomass-based power plants. This research analyzes the potential of utilizing waste as raw material for biomass briquettes to generate electricity. The waste used consists of organic materials processed into briquettes with specific characteristics, such as moisture content, calorific value, and density, to optimize combustion. The study was conducted as a case study on a small-scale biomass-based power plant. An analysis results show that waste briquettes have significant potential as a renewable energy source with relatively high conversion efficiency. Utilizing waste briquettes not only reduces the volume of waste sent to landfills but also lowers greenhouse gas emissions compared to fossil fuels. This study provides recommendations for improving briquette production technology and optimizing combustion systems to achieve better efficiency in biomass power plants.